Passenger Destination System for Commercial Vehicles - Benjamin Kommey; Elvis Tamakloe; Eric Tutu Tchao (IJAIT (International Journal of Applied Information Technology), 2021)
Public vehicles are predominantly the commonest and most widely used means of transport for humans in this current time. However, passengers who often commute with public vehicles mostly encounter the challenge of missing their destination primarily due to difficulties in communicating their destination to the driver, sleeping in the case of long-distance travel or the inability to recognize their destinations, and many more. In this paper, a fully functional and cost-effective passenger destination alert system for commercial vehicles (PDSCV) was developed. This designed passenger destination alert system provides solutions to the problems and as well meets the needs of some target groups such as the physically challenged. To solve these challenges, a GPS-based location module interfaced with a microcontroller unit was employed in the hardware prototype design. Destination stations were displayed and announced via an LCD and audio system respectively to generally alert all passengers on board the vehicle. The prototype also includes alert buttons beside every seat which were to be used by passengers in emergencies and to alert the driver to skip a particular terminal provided the bus is fully occupied and no passenger intends to alight. In addition to the hardware prototype, a software application was developed to provide further information to first-time travellers. The test and results from the entire system indicate a bridge in the communication gap between the driver and the passengers of commercial vehicles.